Effects of mixing and sodium formate on thermophilic in-situ biogas upgrading by H2 addition. (10th April 2019) - Zhu, Xianpu; Cao, Qin; Chen, Yichao; Sun, Xiaoying; Liu, Xiaofeng; Li, Dong
Abstract: The effects of hydrogen (H2 ) injection amount, mixing, and sodium formate on in-situ biogas upgrading performance and microbial community structure were investigated during thermophilic digestion of pig manure in a continuous stirred tank reactor with a working volume of 11.2 L and an organic loading rate of 2.0 g volatile solid (VS)/(L∙d). Continuous mixing was favorable for in-situ biogas upgrading. The relative methane content and methane yield were maintained at approximately 80% and 269 L/kg VS, respectively, under continuous mixing conditions with an H2 injection rate of 0.66 ml/(min∙VReactor ) and an H2 :CO2 ratio of 4:1. The added H2 inhibited acetate production, but not propionate production, during acidogenesis. Sodium formate was more beneficial for the acetogenesis of propionate degradation and restored system stability. Strictly hydrogenotrophic methanogens ( Methanoculleus, Methanobrevibacter, and Methanobacterium ) were dominant in the thermophilic in-situ biogas upgrading system. The syntrophic relationship between syntrophic acetate-oxidizing bacteria ( Gelria ) and hydrogenotrophic methanogens was weakened after the addition of H2 . Graphical abstract: Image 1 Highlights: Continuous mixing was favorable for thermophilic in-situ biogas upgrading by H2 . The RMC and MY was 80% and 269 L/kg VS under continuous mixing, respectively. H2 added inhibited acetate production but not propionate during acidogenesis. Formate was more benefit for acetogenesis of propionate degradation compared to H2 . After H2 added, strict HM plays a key role in in-situ biogas upgrading system.